SECONDARY CRIMINAL LIABILITY IN THE CUSTOMS FIELD: AN EFFORT OF HANDLING OF E-COMMERCE CHALLENGES IN INDONESIA - Sinaga, Henry Dianto P.; Sinaga, Benny R. P. (Journal of Tax Law and Policy, 2023)
The complexities of cross-border e-commerce transactions have created its own challenges for customs authorities. The complexities relating to the traffic of goods entering or leaving a country's territory as well as violations in terms of import duties and export duties will give rise to liability. Based on doctrinal legal research using agency theory, which is useful in solving problems due to conflicting desires or goals and asymmetry of information between principals and agents, then 2 (two) main conclusions are obtained. First, secondary liability in the customs sector currently tends to be limited to administrative liability, which only reaches the Freight and Portage Services Company (PPJK), Designated Postal Operators, and Courier Service Companies (PJT). Second, the justification of secondary criminal liability in the field of customs in handling the challenges of e-commerce in Indonesia must be done through the expansion of participant-based and/or relationship-based meanings that are able to reach PPJK, Postal Operator, PJT, and Platform. It is suggested that there is the formulation of secondary criminal liability. Elements needed to make a claim for secondary criminal liability, as well as relevant standards relating to secondary criminal liability and primary criminal liability.